Cathode material and method of manufacturing the same, lithium-ion battery and electrical device
The cathode material Li 1+a1(Ni x1Co y1Mn z1M 1 m1)M 2 m2O2, manufactured through controlled sintering, addresses cracking issues during rolling, enhancing structural stability and cycle performance in lithium-ion batteries.
Patent Information
- Application Number
- KR1020257043453
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Cathode materials in lithium-ion batteries crack during the electrode sheet rolling process due to crystal plane sliding and layer shifting under pressure, leading to irreversible capacity loss and degradation of cycle performance, despite existing solutions focusing on body-phase doping and surface coating.
A cathode material composition of Li 1+a1(Ni x1Co y1Mn z1M 1 m1)M 2 m2O2 with controlled micro-deformation and a manufacturing method involving precise temperature gradient sintering to reduce internal stress, ensuring better structural stability and fewer cracks during rolling.
The cathode material exhibits improved structural stability, reduced cracking, and enhanced cycle performance, with better processability and increased energy density.
Smart Images

Figure 112025147846337-PCT00004_ABST
Abstract
Description
Technology Field
[0001] This disclosure belongs to the field of battery technology and, specifically, relates to a cathode material and a method for manufacturing the same, a lithium-ion battery, and an electrical device. Background Technology
[0002] Cathode materials are widely used in lithium-ion batteries due to their advantages, such as high energy density, long cycle life, and low gas generation. Failure analysis of cathode materials revealed that, unlike aggregated material particles which fragment and fracture after long-term charge-discharge cycles, cathode materials maintain an intact structure even after multiple charge-discharge cycles, although cracks were found on the surface of some particles. The presence of these cracks exposes the uncoated inner surface to the electrolyte, accelerating corrosion and electrolyte consumption, and leading to irreversible loss of material capacity and degradation of cycle performance.
[0003] The reason for cracking in cathode materials is generally attributed to physicochemical properties during battery usage, namely volume shrinkage / expansion during charging and discharging, intensified polarization due to long lithium ion diffusion paths, and electrolyte decomposition and corrosion caused by excessive operating voltage. However, research indicates that cracking is not the primary cause of cracking, as cracks are still observed even when the cathode material is manufactured into a cathode sheet without undergoing charging and discharging. Cracking is primarily caused by the electrode sheet rolling process, in which cracks occur as crystal planes slide, layers shift, and tears under pressure.
[0004] Existing ideas for cathode material development focus on body-phase doping, surface coating, and shape control, and improve cycle performance by enhancing lithium-ion transport kinetics and reducing side reactions between the cathode material and the electrolyte. However, an effective solution has not yet been established for the problem of crack formation after rolling of the cathode material.
[0005] This disclosure aims to solve at least one of the technical problems of the relevant technology. To this end, this disclosure proposes a cathode material having low stress or high pressure resistance, a method for manufacturing the same, a lithium-ion battery, and an electrical device.
[0006] The first aspect of this disclosure proposes a cathode material, wherein the cathode material is Li 1+a1 (Ni x1 Co y1 Mn z1 M 1 m1 )M 2 m2 Includes O2,
[0007] Here, -0.1≤a1≤0.1, 0.5≤x1<1, 0<y1≤0.4, 0<z1≤0.6, 0≤m1≤0.1, 0≤m2≤0.02, and;
[0008] M 1 ... comprises at least one of Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, Ba, and B;
[0009] M 2 It comprises at least one of W, Mo, Zr, Al, V, Ti, B, Co, and Nb;
[0010] Pressure P of the above anode material x - Micro-deformation change △N Px The fitting line of is △N Px =kP x Satisfies, and 0 <k<0.0012이며;
[0011] Here, k is the slope, P x is a pressure in units of MPa applied to the cathode material before testing micro-deformation, and the micro-deformation change △N Px is pressure P x It is the difference between the micro-deformation of the above-mentioned cathode material after applying pressure and the micro-deformation of the above-mentioned cathode material without applying pressure.
[0012] This disclosure analyzes the structure of a single-crystal multi-component cathode material using an X-ray diffraction analyzer, calculates the micro-deformation of the material through precise correction calculations, evaluates the properties of the material by testing micro-deformation under different pressures, and further evaluates the structural stability of the cathode material. With the above composition, pressure P x - Micro-deformation change △N Px When the fitting straight line satisfies the above conditions, this cathode material has better structural stability and processability, and there are fewer cracks on the particle surface after rolling the electrode sheet, and the cycle performance is significantly improved.
[0013] In some embodiments, 0 <k<0.001이다. k 값이 이 범위 내에 있으면, 양극재의 미세 변형 변화 정도가 약함을 의미하며, 이는 재료 구조가 더 안정적임을 나타내어 고전압 충방전 테스트에서 재료가 구조적 안정성을 유지하도록 보장하여 사이클 성능을 크게 향상시킨다.
[0014] In some embodiments, the microdeformation N of the anode material to which the above pressure is not applied. P0 <0.1%; and in some other embodiments, N P0 It is <0.08%. Accordingly, this cathode material has relatively small micro-deformation, better structural stability, and relatively high pressure resistance.
[0015] In some embodiments, micro-deformation N of the anode material after applying a pressure of 500 MPa. P500 <0.18%; and in some other embodiments, N P500 It is <0.16%. Accordingly, this cathode material has relatively small microdeformation, better structural stability, and relatively high pressure resistance.
[0016] In some embodiments, D of the anode material when no pressure is applied 50 Particle size D 50(P0) D of the above cathode material when a pressure of 500 MPa is applied 50Particle size D 50(P500) Eun (D 50(P0) -D 50(P500) ) / D 50(P0) Satisfies <30%; in some other embodiments, D 50(P500) Eun (D 50(P0) -D 50(P500) ) / D 50(P0) It is <20%. Accordingly, the pressure resistance and cycle performance of the cathode material can be further improved.
[0017] In some embodiments, D of the anode material when no pressure is applied 50 Particle size D 50(P0) is 2 to 6 μm; in some other embodiments, D 50(P0) The value is 2.5 to 4.5 μm. Accordingly, this is advantageous for improving the energy density of lithium-ion batteries.
[0018] In some embodiments, the particle size distribution width of the anode material when no pressure is applied SPAN P0 0.8 P0 Satisfies <1.4; in some other embodiments, 0.9 P0 <1.3 and; here, SPAN P0 =(D 90(P0) -D 10(P0) ) / D 50(P0) is, D 10(P0) D of the above cathode material when no pressure is applied 10 Particle size, D 50(P0) D of the above cathode material when no pressure is applied 50 Particle size, D 90(P0) D of the above cathode material when no pressure is applied 90 It is the particle size. Accordingly, it is advantageous for improving the compressive density and volumetric energy density of the cathode material.
[0019] In some embodiments, the specific surface area S of the anode material when no pressure is applied P0 and the specific surface area S of the anode material when a pressure of 500 MPa is applied P500 Eun, (S P500 -S P0 ) / S P0 Satisfying <75%; in some other embodiments (S P500 -S P0 ) / S P0 It is <50%. Accordingly, the pressure resistance and cycle performance of the cathode material can be further improved.
[0020] In some embodiments, the specific surface area S of the anode material when no pressure is applied P0 is 0.3~1.2 m 2 / g and; in some other embodiments, S P0 is 0.4~1.0 m 2 It is / g. Accordingly, it is advantageous for improving the cycle performance of lithium-ion batteries.
[0021] A second aspect of the present disclosure proposes a method for manufacturing a cathode material, wherein the method for manufacturing the cathode material is,
[0022] Precursor, lithium source, and optionally M 1 A step of mixing the source to obtain a raw material mixture;
[0023] A step of obtaining a primary sintered product by performing primary sintering on the above raw material mixture - the primary sintering includes heating the above raw material mixture to a first temperature T1 and holding it for a first time, then lowering the temperature from T1 to 600℃ at an average cooling rate of ≤2℃ / min, and then naturally cooling it to room temperature - ;
[0024] The above primary sintered product and the first M 2 It includes the step of mixing the source and performing secondary sintering on the obtained mixture to obtain a secondary sintered product.
[0025] This disclosure describes a method for manufacturing an anode material with low stress and high internal pressure strength by controlling the temperature gradient of high-temperature solid-state sintering. This anode material exhibits better processability, fewer cracks on the grain surface after electrode sheet rolling, and significantly improved cycle performance. The key to this manufacturing method lies in controlling the cooling rate; by performing medium-to-high temperature holding annealing during the final stage of high-temperature sintering, internal stress is removed from the anode material, thereby enhancing its internal pressure strength.
[0026] In some embodiments, the first sintering comprises heating the raw material mixture to a first temperature T1 and holding it for a first time, then cooling it from T1 to T1-80℃ at an average cooling rate of ≤1℃ / min, then cooling it from T1-80℃ to 600℃ at an average cooling rate of ≤2℃ / min, and then cooling it naturally to room temperature.
[0027] In some embodiments, T1-80℃ > 800℃, and the temperature is lowered from T1-80℃ to 800℃ at an average cooling rate of ≤1.5℃ / min, then lowered from T1-80℃ to 600℃ at an average cooling rate of ≤2℃ / min, and then naturally cooled to room temperature.
[0028] In some embodiments, 600℃≤T1-80℃≤800℃, and the temperature is lowered from T1-80℃ to 600℃ at an average cooling rate of ≤2℃ / min, and then naturally cooled back to room temperature.
[0029] When the above sintering conditions are satisfied, it is advantageous to obtain a cathode material with relatively low stress and relatively high pressure resistance, and furthermore, improves the cycle performance of lithium-ion batteries.
[0030] In some embodiments, the method for manufacturing the anode material comprises the secondary sintered product and the second M 2 The method further includes the step of mixing the source and performing a third sintering on the obtained mixture to obtain a third sintered product. Accordingly, the energy density and cycle performance of the cathode material can be further improved.
[0031] In some embodiments, the lithium source comprises one of lithium carbonate, lithium hydroxide, anhydrous lithium hydroxide, and lithium oxide. Accordingly, the source of the material raw material is broad and the cost is relatively low.
[0032] In some embodiments, the above M 1 The source is M 1 It includes at least one of elemental oxides, carbonates, phosphates, fluorides, chlorides, hydroxides, and silicides. Accordingly, the source of material raw materials is wide and the cost is relatively low.
[0033] In some embodiments, the first M 2 Source and the 2nd M 2 The sources are each independently M 2 It includes at least one of elemental oxides, carbonates, phosphates, fluorides, chlorides, hydroxides, and silicides. Accordingly, the source of material raw materials is wide and the cost is relatively low.
[0034] In some embodiments, the temperature of the secondary sintering is 400 to 800°C, and the holding time is 4 to 10 hours.
[0035] In some embodiments, the temperature of the third sintering is 300 to 600°C, and the holding time is 4 to 10 hours.
[0036] The third aspect of the present disclosure proposes a lithium-ion battery comprising a cathode material according to the first aspect of the present disclosure or a cathode material manufactured by the method according to the second aspect of the present disclosure. Accordingly, the lithium-ion battery has relatively good cycle performance.
[0037] The fourth aspect of the present disclosure proposes an electric device comprising a lithium-ion battery according to the third aspect of the present disclosure. Accordingly, the electric device has a relatively long service life. Brief explanation of the drawing
[0038] Figure 1 is a schematic diagram of the sintering curve by the temperature gradient of the present disclosure. Figure 2 is an SEM image of the cathode material of the present disclosure after rupturing it under a pressure of 500 MPa. Specific details for implementing the invention
[0039] Embodiments of the present disclosure have been described in detail below, and examples of such embodiments are illustrated in the drawings. The embodiments described below with reference to the drawings are illustrative and are intended to be interpreted as a limitation to the present disclosure, not to be understood as a limitation to the present disclosure.
[0040] The first aspect of this disclosure proposes a cathode material, wherein
[0041] This cathode material is Li 1+a1 (Ni x1 Co y1 Mn z1 M 1 m1 )M 2 m2 Includes O2,
[0042] Here, -0.1≤a1≤0.1, 0.5≤x1<1, 0<y1≤0.4, 0<z1≤0.6, 0≤m1≤0.1, 0≤m2≤0.02, and;
[0043] M 1 ... comprises at least one of Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, Ba, and B;
[0044] M 2 It comprises at least one of W, Mo, Zr, Al, V, Ti, B, Co, and Nb;
[0045] Pressure P of the above anode material x - Micro strain change △N Px The fitting line of is △N Px =kP x Satisfies, and 0 <k<0.0012이며;
[0046] Here, k is the slope, P xis a pressure in units of MPa applied to the cathode material before testing micro-deformation, and the micro-deformation change △N Px is pressure P x It is the difference between the micro-deformation of the above-mentioned cathode material after applying pressure and the micro-deformation of the above-mentioned cathode material without applying pressure.
[0047] This disclosure analyzes the structure of an anode material using an X-ray diffraction analyzer, calculates the micro-deformation of the material through precision refinement calculations, evaluates the properties of the material by testing micro-deformation under different pressures, and further evaluates the structural stability of the anode material. The anode material of this disclosure is 0 <k<0.0012를 만족하므로, 미세 변형 변화 정도가 작고, 비교적 좋은 구조적 안정성과 가공성능을 가지며, 전극시트 롤링 후 입자 표면에 발생하는 균열이 더욱 적고, 사이클 성능이 현저히 향상된다.
[0048] In some embodiments, 0 <k<0.001이며, 예를 들어 0.0001, 0.0002, 0.0003, 0.0004, 0.0005, 0.0006, 0.0007, 0.0008, 0.0009 또는 0.001 등일 수 있다. 여기서, k 값의 크기는 재료의 서로 다른 압력 조건 하에서의 미세 변형 변화 정도를 반영하며, k 값이 낮을수록 압력이 증가함에 따라 재료의 미세 변형 변화 정도가 약해짐을 의미하는 바, 이는 재료 구조가 더 안정적임을 나타내며, k 값이 낮은 재료일 수록 고전압 충방전 테스트에서 재료의 구조적 안정성을 유지하도록 보장하여 사이클 성능을 크게 향상시킬 수 있다.
[0049] In this text, the pressure P of the above-mentioned cathode material x and micro-deformation change △N Px The method for fitting to a straight line includes the following steps:
[0050] Step 1: n parts of a cathode material are taken, and the n parts of the said cathode material are defined as a first part cathode material, a second part cathode material, ......, an n-th part cathode material, where n is an integer greater than or equal to 5;
[0051] Step 2: The first part anode material, the second part anode material, ......, and the nth part anode material are each placed into a mold, and a first pressure, a second pressure, ......, and the nth pressure are applied in a one-to-one correspondence, sequentially increasing from small to large, and the obtained compressed specimen is separated to obtain a first sample, a second sample, ......, and the nth sample in correspondence, and the anode material to which no pressure is applied constitutes an initial sample;
[0052] Step 3: After performing equipment goniometer position calibration and instrument width calibration for the X-ray powder diffraction analyzer, X-ray diffraction tests are performed on the initial sample, the first sample, the second sample, ......, the nth sample, respectively, using the X-ray powder diffraction analyzer to obtain X-ray diffraction data;
[0053] Step 4: Based on the X-ray diffraction data, the micro-deformation N corresponding to the initial sample, the first sample, the second sample, ......, the nth sample P0 , N P1 , N P2 , ......, N Pn After calculating, the micro-deformation change △N for each P1 =N P1 -N P0 , △N P2 =N P2 -N P1 , ......, △N Pn =N Pn -N Pn-1 Producing;
[0054] Step 5: Create a scatter plot for the micro-deformation change and the pressure intensity, fit a straight line, and determine the structural stability of the anode material based on the slope of the fitted straight line.
[0055] It should be noted that the pressure applied to the cathode material must be within a reasonable range. In some embodiments, the pressure P1 of the cathode material is 50 to 150 MPa (e.g., 50 MPa, 80 MPa, 100 MPa, 120 MPa, or 150 MPa, etc.). In other embodiments, the pressure P1 of the cathode material is 80 to 120 MPa.
[0056] In some embodiments, the pressure P of the anode material n is 150 to 900 MPa (e.g., 150 MPa, 200 MPa, 300 MPa, 400 MPa, 500 MPa, 600 MPa, 700 MPa, 800 MPa, or 900 MPa, etc.). In some other embodiments, the pressure P of the cathode material n It is 160~600MPa.
[0057] In some embodiments, the pressure P of the anode material i and P i-1 The difference value is 20 to 200 MPa (e.g., 20 MPa, 40 MPa, 60 MPa, 80 MPa, 100 MPa, 120 MPa, 140 MPa, 160 MPa, 180 MPa, or 200 MPa, etc.). In some other embodiments, the difference value is 50 to 100 MPa, where i is an integer from 2 to n, and n is an integer greater than or equal to 5 (e.g., 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15, etc.).
[0058] As an example, when n=7, the pressure P of the above anode material x and micro-deformation change △N Px The method for fitting to a straight line specifically includes the following steps:
[0059] Step 1: Moisture-treat the surface of the cathode material, generally drying it at 100°C for 2 hours using a drying oven or vacuum oven.
[0060] Step 2: Weigh the sample, and take the treated sample according to the following criteria: D 50For samples with ≤3μm, the sample amount is 0.5–1.5g; and 3μm≤D 50 For samples with ≤7μm, the sample amount is 1.5~3g; D 50 For samples with a size of ≥7μm, the sample weight is 3 to 5g. Transfer the weighed sample to a compression mold and gently shake the mold to flatten the surface of the sample.
[0061] Step 3: Place the mold containing the sample in the equipment and gradually pressurize it to a specified pressure (specifically, pressures of 50 MPa, 100 MPa, 200 MPa, 300 MPa, 400 MPa, 500 MPa, and 600 MPa pressure intensity), where pressure applied by the equipment / mold area = pressure intensity, stop for 30 seconds, then remove and demold the sample. Only one pressure point can be measured per sample preparation.
[0062] Step 4: Place the demolded anode compressed specimen into a mortar, gently separate the specimen, and sift the particles using a standard sieve so that the specimen is completely powdered and there are no sheet-like particles. Then, place the treated sample in a bag, label it, and store it.
[0063] Step 5: Perform parameter calibration of the X-ray powder diffraction analyzer instrument, wherein instrument goniometer position calibration is performed using standard Si powder and instrument width calibration is performed using standard LaB6;
[0064] Under verified test conditions, perform goniometer position and instrument width calibration respectively, prepare a standard (Si powder, LaB6) on the sample stage, collect the spectrum, perform instrument calibration, and save the data.
[0065] Step 6: Prepare materials with different pressures on a sample stage, perform X-ray powder diffraction tests under verified conditions, save the data, and await analysis; the samples prepared on the sample stage must be flat and ensure that the sample height is consistent each time.
[0066] Step 7: Import test data into fine-tuning software and perform data processing:
[0067] (1) First, perform peak position processing, select and process the maximum peak value, and ensure that the software recognizes all peak positions;
[0068] (2) Perform image identification, verify the image using the PDF5+ database (International Diffraction Data Center), and require that the test data and card information maintain high consistency;
[0069] (3) Add instrument width calibration data (external standard calibration width), select all crystal planes, and calculate the microstress data of the material using the Halder-Wagner method.
[0070] Step 8: Analyze the micro-deformation data of the material calculated according to the Halder-Wagner method.
[0071] Step 9: Create and analyze a scatter plot of micro-deformation data and pressure, and calculate the slope k.
[0072] In some embodiments, the microdeformation N of the anode material to which the pressure is not applied. P0 It is <0.1% and may be, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, or 0.09%, etc. In some other embodiments, N P0 It is <0.08%. If the micro-deformation is within the above range, it explains that the structural stability of this cathode material is relatively good and it has relatively high pressure resistance.
[0073] In some embodiments, micro-deformation N of the anode material after applying a pressure of 500 MPa. P500 It is <0.18% and may be, for example, 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.13%, 0.15%, or 0.17%, etc. In some other embodiments, N P500It is <0.16%. After applying pressure, the micro-deformation of this cathode material is relatively small, and it has a relatively high pressure resistance.
[0074] In some embodiments, D of the anode material when no pressure is applied 50 Particle size D 50(P0) D of the above cathode material when a pressure of 500 MPa is applied 50 Particle size D 50(P500) Eun (D 50(P0) -D 50(P500) ) / D 50(P0) Satisfying <30%, it may be, for example, 1%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, or 28%, etc. In some other embodiments, (D 50(P0) -D 50(P500) ) / D 50(P0) It is <20%. Accordingly, the pressure resistance and cycle performance of the cathode material can be further improved.
[0075] In some embodiments, D of the anode material when no pressure is applied 50 Particle size D 50(P0) The is 2 to 6 μm, and may be, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, or 6 μm, etc. In some other embodiments, D of the cathode material when no pressure is applied 50 Particle size D 50(P0) The value is 2.5 to 4.5 μm. Accordingly, this is advantageous for improving the energy density of lithium-ion batteries.
[0076] In some embodiments, the particle size distribution width of the anode material when no pressure is applied SPAN P0 0.8 P0 It satisfies <1.4 and may be, for example, 0.9, 1, 1.1, 1.2, or 1.3, etc. In some other embodiments, 0.9 P0 It is <1.3. Here, SPAN P0 =(D 90(P0) -D 10(P0) ) / D 50(P0) is, D10(P0) D of the above cathode material when no pressure is applied 10 Particle size, D 50(P0) D of the above cathode material when no pressure is applied 50 Particle size, D 90(P0) D of the above cathode material when no pressure is applied 90 It is the particle size. If the particle size distribution width is within the above range, it is advantageous for improving the compressive density and volumetric energy density of the cathode material.
[0077] In the particle size distribution, D 50 is also called the median particle size, and means that the particle size of 50 volume percent is smaller than or equal to this value, and D 90 means that the particle size of 90 volume percent is smaller than or equal to this value, and D 10 means that the particle size of 10 volume% is smaller than or equal to this value. D 10 , D 50 , D 90 This can be measured using a Malvern particle size analyzer: Disperse the cathode material in a dispersant (ethanol, acetone, or other surfactant), sonicate for 30 minutes, then place the sample into the Malvern particle size analyzer and start the test.
[0078] In some embodiments, the specific surface area S of the anode material when no pressure is applied P0 and the specific surface area S of the anode material when a pressure of 500 MPa is applied P500 Eun, (S P500 -S P0 ) / S P0 Satisfies <75%, and may be, for example, 10%, 20%, 30%, 40%, 50%, 60%, or 70%, etc. In some other embodiments, (S P500 -S P0 ) / S P0 It is <50%.
[0079] In some embodiments, the specific surface area S of the anode material when no pressure is applied P0 is 0.3~1.2 m2 / g, for example, 0.3 m 2 / g, 0.4 m 2 / g, 0.5 m 2 / g, 0.6 m 2 / g, 0.7 m 2 / g, 0.8 m 2 / g, 0.9 m 2 / g, 1 m 2 / g, 1.1 m 2 / g or 1.2 m 2 It may be / g, etc. In some other embodiments, S P0 is 0.4~1.0 m 2 It is / g. Accordingly, it is advantageous for improving the cycle performance of lithium-ion batteries.
[0080] In this text, the specific surface area of the cathode material refers to the surface area of the cathode material per unit mass, and S P0 and S P500 It can be measured using a specific surface area measuring instrument.
[0081] A second aspect of the present disclosure proposes a method for manufacturing a cathode material comprising the following steps:
[0082] S1: Precursor, lithium source, and optionally M 1 Mix the sauces to obtain a mixture of raw materials.
[0083] At this stage, a precursor, a lithium source, and optionally M 1 The specific method of mixing the sauce is not particularly limited, and, for example, a mixer can be used. At this stage, M as needed 1 It can be understood that you can flexibly choose whether or not to add the sauce.
[0084] In some embodiments, the lithium source comprises one of lithium carbonate, lithium hydroxide, anhydrous lithium hydroxide, and lithium oxide. Accordingly, the source of the material raw material is broad and the cost is relatively low.
[0085] In some embodiments, the above M 1 The source is M 1It includes at least one of elemental oxides, carbonates, phosphates, fluorides, chlorides, hydroxides, and silicides. Accordingly, the source of material raw materials is wide and the cost is relatively low.
[0086] S2: A first sintering is performed on the above raw material mixture to obtain a first sintered product, wherein the first sintering includes heating the raw material mixture to a first temperature T1 and holding it for a first time, then lowering the temperature from T1 to 600℃ at an average cooling rate of ≤2℃ / min, and then naturally cooling it to room temperature.
[0087] Here, the average cooling rate must be calculated by dividing the total temperature difference from T1 to 600℃ by the total time taken to cool from T1 to 600℃. The specific implementation process may use a continuous cooling method or a method of maintaining a constant temperature by setting an intermediate temperature. During the cooling process, it is permitted for the instantaneous cooling rate of the cooling process in any section to exceed 2℃ / min, and the requirements of this patent are met as long as the average cooling rate from T1 to 600℃ is ≤2℃ / min, and the same applies to the average cooling rate of the process described below.
[0088] In some embodiments, the first sintering comprises: heating the raw material mixture to a first temperature T1 and holding it for a first time, then cooling it from T1 to T1-80℃ at an average cooling rate of ≤1℃ / min, then cooling it from T1-80℃ to 600℃ at an average cooling rate of ≤2℃ / min, and then naturally cooling it to room temperature;
[0089] If T1-80℃ > 800℃, the temperature is lowered from T1-80℃ to 800℃ at an average cooling rate of ≤1.5℃ / min, then lowered from T1-80℃ to 600℃ at an average cooling rate of ≤2℃ / min, and then naturally cooled to room temperature;
[0090] When 600℃≤T1-80℃≤800℃, the temperature is lowered from T1-80℃ to 600℃ at an average cooling rate of ≤2℃ / min, and then naturally cooled back to room temperature.
[0091] When the cooling rate is within the above range, the distribution of metal elements within the multicomponent cathode material body is made more uniform, problems such as lattice defects and crystal segregation caused by an excessively fast cooling rate are effectively improved, the concentration of internal micro-deformations is reduced, and the layered structure is further stabilized.
[0092] It should be explained that the specific cooling program of this disclosure is not particularly limited and can be divided into different stages. As an example, referring to FIG. 1, the raw material mixture is heated to a first temperature T1 and held for a first time, then cooled from T1 to T2 at an average cooling rate of v2, then cooled again from T2 to T3 at an average cooling rate of v3, and finally cooled from T3 to T4 at an average cooling rate of v4, and held for a certain time to obtain a first sintered product.
[0093] S3: The above primary sintered product and the first M 2 The source is mixed, and secondary sintering is performed on the obtained mixture to obtain a secondary sintered product.
[0094] At this stage, the primary sintered product and the first M 2 The specific method of mixing the sauce is not particularly limited, and, for example, it can be mixed using a mixer.
[0095] In some embodiments, the method for manufacturing the cathode material further comprises: the secondary sintered product and the second M 2 The source is mixed, and a third sintering is performed on the obtained mixture to obtain a third sintered product.
[0096] In some embodiments, the first M 2 Source and the 2nd M 2 The sources are each independently M 2It includes at least one of elemental oxides, carbonates, phosphates, fluorides, chlorides, hydroxides, and silicides. Accordingly, the source of material raw materials is wide and the cost is relatively low.
[0097] In some embodiments, the temperature of the secondary sintering is 400 to 800°C (e.g., 400°C, 500°C, 600°C, 700°C, or 800°C, etc.), and the holding time is 4 to 10 hours (e.g., 4h, 5h, 6h, 7h, 8h, 9h, or 10h, etc.).
[0098] In some embodiments, the temperature of the third sintering is 300 to 600°C (e.g., 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, or 600°C, etc.), and the holding time is 4 to 10 hours (e.g., 4h, 5h, 6h, 7h, 8h, 9h, or 10h, etc.).
[0099] This disclosure controls the temperature gradient of high-temperature solid-state sintering and increases the holding time in the medium-high temperature range above 600°C (i.e., lowers the cooling rate), thereby making the distribution of metal elements within the cathode material more uniform, effectively improving problems such as lattice defects and crystal segregation caused by an excessively fast cooling rate, reducing the concentration of internal micro-deformation, and further stabilizing the layered structure to produce a cathode material having low stress and high internal pressure strength. This cathode material has better processability, fewer cracks on the grain surface after rolling the electrode sheet, and significantly improved cycle performance. This manufacturing method removes internal stress and improves the internal pressure strength of the cathode material by performing medium-high temperature holding annealing at the final stage of high-temperature sintering through cooling rate control; furthermore, the process is simple and controllable, has low production costs, and enables large-scale production.
[0100] The third aspect of the present disclosure proposes a lithium-ion battery comprising a cathode material according to the first aspect of the present disclosure or a cathode material manufactured by the method according to the second aspect of the present disclosure. Accordingly, the lithium-ion battery has relatively good cycle performance.
[0101] As can be understood, the specific type of this lithium-ion battery is not particularly limited and may be a primary battery or a secondary battery. The shape of this lithium-ion battery may be a cylindrical battery, a prismatic battery, or any other battery of any shape, and when classified according to the external packaging, the lithium-ion battery may be a hard-case type battery, a pouch type battery, etc.
[0102] Generally, a lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. Here, the positive electrode sheet, negative electrode sheet, and separator can be manufactured into an electrode assembly through a winding or lamination process, and the electrode assembly and electrolyte can be housed within an outer package. During the charging and discharging process of a lithium-ion battery, active ions reciprocate between the positive electrode sheet and the negative electrode sheet to be inserted and removed. The electrolyte serves to conduct ions between the positive electrode sheet and the negative electrode sheet. The separator is installed between the positive electrode sheet and the negative electrode sheet and primarily serves to prevent short circuits between the positive and negative electrodes while simultaneously allowing active ions to pass through.
[0103] In some embodiments, the anode sheet may comprise an anode current collector and an anode active material layer installed on at least one surface of the anode current collector, and the anode active material layer comprises an anode active material, a conductive agent, and a binder. The anode current collector may comprise a metal foil, for example, aluminum foil may be used for the metal foil. The anode active material may comprise an anode material according to the first aspect of this disclosure or an anode material manufactured by the method according to the second aspect of this disclosure. The conductive agent may comprise acetylene black, single-walled carbon nanotubes, and materials conventional in the art. The binder may be polyvinylidene fluoride (PVDF) and materials conventional in the art.
[0104] In some embodiments, the cathode sheet may include a cathode current collector and a cathode active material layer installed on at least one surface of the cathode current collector, and the cathode active material layer may include a cathode active material, a thickener, a conductive agent, and a binder. Here, the cathode current collector may use a metal foil, for example, the metal foil may use copper foil. The cathode active material may include artificial graphite, natural graphite, silicon-containing carbon-based composite material, lithium-containing metal composite material, lithium metal material, and cathode active material commonly used in the art. The thickener may be sodium carboxymethyl cellulose (CMC-Na) and a material commonly used in the art. The conductive agent may be acetylene black and a material commonly used in the art. The binder may be styrene butadiene rubber and a material commonly used in the art.
[0105] In some embodiments, the separator may be used in a lithium-ion battery and may be a separator known in the art that is stable with respect to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, etc.
[0106] The fourth aspect of the present disclosure proposes an electric device comprising a lithium-ion battery according to the third aspect of the present disclosure. Accordingly, the electric device has a relatively long service life.
[0107] In some embodiments, the lithium-ion battery may be used as a power source for the electric device or as an energy storage unit for the electric device. The electric device may include, but is not limited to, mobile devices (e.g., mobile phones, laptop computers, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0108] The embodiments of the present disclosure are described in detail below.
[0109] Example 1
[0110] (1) Multicomponent material precursor Ni 0.6 Co 0.1 Mn 0.3 (OH)2 and lithium carbonate are uniformly mixed, high-temperature solid-state sintering is performed at 1000℃ and held for 10 hours, then cooled to 920℃ at a rate of 0.5℃ / min, then cooled again to 800℃ at a rate of 1℃ / min, then cooled again to 600℃ at a rate of 2℃ / min, then naturally cooled to room temperature, and after grinding and sieving, a primary sintered product is obtained;
[0111] (2) The primary sintered product and the coating agent Al2O3 are uniformly mixed, heat treatment is performed at 500°C and held for 8 hours, and then crushed and sieved to obtain a single-crystal multi-component cathode material.
[0112] Examples 2 to 23
[0113] It is identical to Example 1, and the specific differences are as shown in Tables 1 and 2.
[0114] Comparative Example 1
[0115] In Example 1, high-temperature solid-state sintering at 1000°C was performed and the temperature was maintained for 10 hours, after which it was naturally cooled to room temperature, and the rest was the same.
[0116] Comparative Example 2
[0117] In Example 1, high-temperature solid-state sintering at 1000°C was performed and the temperature was maintained for 10 hours, then the temperature was lowered to 600°C at a rate of 4°C / min, and then naturally cooled to room temperature, and the rest is the same.
[0118] The specific parameters of the above examples and comparative examples are as shown in Table 1 and Table 2.
[0119] Cathode material chemical composition Chemical composition Lia1 Nix1 Coy1 Mnz1 M 1 m1 M 2 m2 M 1 M 2 Example 1 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Al Example 2 Li 0.9 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 -0.1 0.6 0.1 0.29 / 0.01 / Al Example 3 Li 1.1 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 0.1 0.6 0.1 0.29 / 0.01 / Al Example 4 Li 1.01 (Ni 0.5 Co 0.2 Mr 0.29 ) 0.01 O2 0.01 0.5 0.2 0.29 / 0.01 / Al Example 5 Li 1.01 (Ni 0.7 Co 0.1 Mr 0.19 ) 0.01 O2 0.01 0.7 0.1 0.19 / 0.01 / Al Example 6 Li 1.01 (Ni 0.8 Co 0.1 Mr 0.09 ) 0.01 O2 0.01 0.8 0.1 0.09 / 0.01 / Al Example 7 Li 1.01 (Ni 0.9 Co 0.05 Mr 0.04 ) 0.01 O2 0.01 0.9 0.05 0.04 / 0.01 / Al Example 8 Li 1.01 (Ni 0.6 Co 0.1 Mn 0.24 Zr 0.05 Al 0.01 O2 0.01 0.6 0.1 0.24 0.05 0.01 Zr Al Example 9 Li 1.01 (Ni 0.6 Co 0.1 Mn 0.19 Zr 0.1 Al 0.01 O2 0.01 0.6 0.1 0.19 0.1 0.01 Zr Al Example 10 Li 0.01 (Ni 0.6 Co 0.1 Mr 0.3 )O2 0.01 0.6 0.1 0.3 / 0 / / Example 11 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.28 ) 0.01 O2 0.01 0.6 0.1 0.28 / 0.02 / Al Example 12 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 )W 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / W Example 13 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) Tea 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Ti Example 14 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 )Co 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Co Example 15 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Al Example 16 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Al Example 17 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.005 F 0.005 O2 0.01 0.6 0.1 0.29 / 0.01 / Al, F Example 18 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.005 No 0.005 O2 0.01 0.6 0.1 0.29 / 0.01 / Al, Nb Example 19 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.005 B 0.005 O2 0.01 0.6 0.1 0.29 / 0.01 / Al, B Example 20 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Al Example 21 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Al Example 22 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Al Example 23 Li 1.01 (Ni 0.9 Co 0.05 Mr 0.04 ) 0.01 O2 0.01 0.9 0.05 0.04 / 0.01 / Al Comparative Example 1 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Al Comparative Example 2 Li 1.01 (Ni 0.6 Co 0.1 Mr 0.29 ) 0.01 O2 0.01 0.6 0.1 0.29 / 0.01 / Al
[0120]
[0121]
[0122] Performance Test:
[0123] 1. Micro strain test:
[0124] Step 1: Surface moisture treatment of the single-crystal multi-component cathode material is performed, generally by drying it at 100 to 150°C for 1 to 2 hours using a drying oven or vacuum oven.
[0125] Step 2: Weigh the sample, and take the treated sample according to the following criteria: D 50 For samples with ≤3μm, the sample amount is 0.5–1.5g; and 3μm≤D 50 For samples with ≤7μm, the sample amount is 1.5~3g; D 50 For samples with a size of ≥7μm, the sample weight is 3 to 5g. Transfer the weighed sample to a compression mold and gently shake the mold to flatten the surface of the sample.
[0126] Step 3: Place the mold containing the sample in the equipment and gradually pressurize it to different pressures (specifically, apply pressures of 50 MPa, 100 MPa, 200 MPa, 300 MPa, 400 MPa, and 500 MPa), then stop for 30 seconds and remove it to demold the sample. Only one pressure point can be measured per sample preparation.
[0127] Step 4: Place the demolded anode compressed specimen into a mortar, gently separate the specimen, and sift the particles using a standard sieve to ensure the specimen is completely powdered and free of sheet-like particles. Then, place the treated sample in a bag, label it, and store it. Standard sieve size: 200–400 mesh.
[0128] Step 5: Perform parameter calibration of the X-ray powder diffraction analyzer instrument, wherein instrument goniometer position correction is performed using standard Si powder and instrument width correction is performed using standard LaB6; the operation is as follows:
[0129] Test conditions: voltage 40kV; current 200mA; step 0.02°; scan angle 5–120°; acquisition time 45 minutes; and a peak intensity greater than 10,000 cps must be acquired.
[0130] Under verified test conditions, perform goniometer position and instrument width calibration respectively, prepare a standard (Si powder, LaB6) on the sample stage, collect the spectrum, perform instrument calibration, and save the data.
[0131] Step 6: Prepare materials with different pressures on a sample stage, perform X-ray powder diffraction tests under verified conditions, save the data, and await analysis; the samples prepared on the sample stage must be flat and ensure that the sample height is consistent each time.
[0132] Step 7: Import test data into fine-tuning software and perform data processing:
[0133] (1) First, perform peak position processing, select and process the maximum peak value, and ensure that the software recognizes all peak positions;
[0134] (2) Perform image identification, verify the image using the PDF5+ database (International Diffraction Data Center), and require that the test data and card information maintain a high degree of agreement;
[0135] (3) Add instrument width calibration data (external standard calibration width), select all crystal planes, and calculate the micro-deformation data of the material using the Halder-Wagner method.
[0136] 2. D 50 Test: Measure using a Malvern Mastersize 2000 laser particle size analyzer.
[0137] 3. Spread of particle size distribution P0 Test: Measure using a Malvern Mastersizer 2000 laser particle size analyzer.
[0138] 4. Specific surface area test: Measure using the Tristar II 3020 model specific surface area meter from Micromertics, USA.
[0139] 5. Cycle Performance Test:
[0140] (1) Battery composition: 9.5g of a positive active material sample, 0.25g of acetylene black, and 0.25g of polyvinylidene fluoride (PVDF) are mixed to form a positive slurry. This is coated onto an aluminum foil and dried, then press-molded to a diameter of 12mm and a thickness of 120μm under a pressure of 100MPa, and then dried in a vacuum drying oven at 120℃ for 12 hours to obtain a positive sheet.
[0141] The cathode uses a Li metal sheet with a diameter of 17 mm and a thickness of 1 mm; the separator uses a polyethylene porous membrane with a thickness of 25 μm; and the electrolyte uses a 1.0 mol / L LiPF6 solution, wherein an equal mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) is used as the solvent.
[0142] This positive electrode sheet, separator, negative electrode sheet, and electrolyte are assembled to make a 2025-type coin battery.
[0143] (2) Capacity retention rate after 80 cycles: The charge / discharge voltage range is controlled to 3.0V to 4.45V, and the coin battery is charged and discharged once at 0.1C under constant temperature of 45℃, and then charged and discharged 80 times at 1C to evaluate the high-temperature cycle capacity retention rate of the cathode material.
[0144] 6. Shape test: Measure using a scanning electron microscope of the S-4800 model from Hitachi, Japan.
[0145] The performance parameters of the cathode active materials prepared in the above examples and comparative examples are as shown in Table 3.
[0146]
[0147] According to the data in Table 3, from the comparison of Examples 1 to 23 and Comparative Examples 1 to 2, it can be seen that the present disclosure effectively lowered micro-deformation of the cathode material and reduced crack occurrence by controlling the temperature gradient of high-temperature solid-state sintering and increasing the holding time in the medium-to-high temperature range of 600°C or higher, and also significantly improved the cycle performance of the lithium-ion battery.
[0148] In the description of this disclosure, the terms “first” and “second” are used solely for descriptive purposes and should not be understood as indicating or implying relative importance, or as implicitly specifying the number of indicated technical features. Accordingly, features limited to “first” and “second” include at least one of such features, either explicitly or implicitly. In the description of this disclosure, the meaning of “plural” is at least two, e.g., two, three, etc., unless clearly and specifically defined otherwise.
[0149] In the description of this specification, descriptions of reference terms such as “one embodiment,” “some embodiment,” “example,” “specific example,” or “some example” mean that specific features, structures, materials, or properties described in conjunction with said embodiment or example are included in at least one embodiment or example of this disclosure. In this specification, general expressions of said terms do not necessarily refer to the same embodiment or example. Furthermore, the described specific features, structures, materials, or properties may be combined in an appropriate manner in any one or more embodiments or examples. Additionally, where not contradictory, those skilled in the art may combine and combine different embodiments or examples and features of different embodiments or examples described in this specification.
[0150] Although the embodiments of the disclosure above have been presented and described, they should be understood as exemplary and not as a limitation to the disclosure, and those skilled in the art may make changes, modifications, substitutions, and variations to the embodiments within the scope of the disclosure.
Claims
Claim 1 Li 1+a1 (Ni x1 Co y1 Mn z1 M 1 m1 )M 2 m2 A cathode material comprising O2, wherein -0.1≤a1≤0.1, 0.5≤x1<1, 0<y1≤0.4, 0<z1≤0.6, 0≤m1≤0.1, 0≤m2≤0.02; and the above M 1 ... comprises at least one of Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, Ba, and B; said M 2 comprises at least one of W, Mo, Zr, Al, V, Ti, B, Co, and Nb; and pressure (P) applied to the cathode material x ) and change in micro-deformation (△N Px The fitting line of ) is △N Px =kP x Satisfies, and here 0 <k<0.0012이고;상기 k는 기울기이고, 상기 P x is a pressure in units of MPa applied to the cathode material before testing micro-deformation, and the micro-deformation change amount (△N Px ) is P x It is the difference value between the micro-deformation of the cathode material after applying pressure and the micro-deformation of the cathode material in a state without applying pressure; and the micro-deformation of the cathode material after applying a pressure of 500 MPa (N P500 ) is N P500 Cathode material with <0.18%. Claim 2 In paragraph 1, the above k is 0 <k<0.001인, 양극재. Claim 3 In claim 1, the micro-deformation (N) of the anode material in a state where the pressure is not applied. P0 ) is N P0 Cathode material with <0.1%. Claim 4 In paragraph 3, an anode material satisfying at least one of the following conditions (i) and (ii): (i) micro-deformation (N) of the anode material in a state where the pressure is not applied. P0 )silver N P0 <0.08%; and (ii) micro-deformation of the cathode material after applying a pressure of 500 MPa (N P500 ) is N P500 <0.16%. Claim 5 In claim 1, D of the anode material in a state where no pressure is applied 50 Particle size (D 50(P0) D of the above cathode material after applying ) and a pressure of 500 MPa 50 Particle size (D 50(P500) ) is (D 50(P0) -D 50(P500) ) / D 50(P0) Cathode material satisfying <30%. Claim 6 In paragraph 5, D of the anode material in a state where the above pressure is not applied. 50 Particle size (D 50(P0) D of the above cathode material after applying ) and a pressure of 500 MPa 50 Particle size (D 50(P500) ) is (D 50(P0) -D 50(P500) ) / D 50(P0) Cathode material satisfying <20%. Claim 7 In claim 1, D of the anode material in a state where no pressure is applied 50 Particle size (D 50(P0) ) is a cathode material having a thickness of 2 to 6 μm. Claim 8 In claim 7, D of the anode material in a state where the above pressure is not applied. 50 Particle size (D 50(P0) A cathode material having a thickness of 2.5 to 4.5 μm. Claim 9 In claim 1, the particle size distribution width (SPAN) of the anode material in a state where no pressure is applied. P0 ) is 0.8 P0 Satisfying <1.4; here, SPAN P0 =(D 90(P0) -D 10(P0) ) / D 50(P0) is, D 10(P0) is D of the above-mentioned cathode material in a state where no pressure is applied. 10 Particle size, D 50(P0) is D of the above-mentioned cathode material in a state where no pressure is applied. 50 Particle size, D 90(P0) is D of the above-mentioned cathode material in a state where no pressure is applied. 90 Cathode material with particle size. Claim 10 In claim 9, the particle size distribution width (SPAN) of the anode material in a state where the above pressure is not applied. P0 ) is 0.9 P0 Cathode material satisfying <1.3. Claim 11 In claim 1, the specific surface area (S) of the anode material in a state where no pressure is applied P0 ) and the specific surface area (S) of the anode material after applying a pressure of 500 MPa P500 ) is (S P500 -S P0 ) / S P0 Cathode material satisfying <75%. Claim 12 In claim 11, the specific surface area (S) of the anode material in a state where the above pressure is not applied. P0 ) and the specific surface area (S) of the anode material after applying a pressure of 500 MPa P500 ) is (S P500 -S P0 ) / S P0 Cathode material satisfying <50%. Claim 13 In claim 1, the specific surface area (S) of the anode material in a state where no pressure is applied P0 ) is 0.3 to 1.2 m 2 / g, cathode material. Claim 14 In Clause 13, the specific surface area (S) of the anode material in a state where the above pressure is not applied P0 ) is 0.4 to 1.0 m 2 / g, cathode material. Claim 15 A method for manufacturing a cathode material according to any one of claims 1 to 14, comprising a precursor, a lithium source, and optionally M 1 The method comprises the steps of: mixing a source to obtain a raw material mixture; and performing a first sintering on the raw material mixture to obtain a first sintered product, wherein the first sintering includes heating the raw material mixture to a first temperature (T1) and holding it for a first time, then lowering the temperature from T1 to 600℃ at an average cooling rate of ≤2℃ / min, and then naturally cooling it to room temperature, and wherein the first sintered product and the first M 2 A method for manufacturing an anode material, comprising the step of mixing a source and performing secondary sintering on the obtained mixture to obtain a secondary sintered product. Claim 16 A method for manufacturing an anode material according to claim 15, wherein the first sintering comprises heating the raw material mixture to a first temperature (T1) and holding it for a first time, then cooling it from T1 to (T1-80)℃ at an average cooling rate of ≤1℃ / min, then cooling it from T1-80℃ to 600℃ at an average cooling rate of ≤2℃ / min, and then naturally cooling it to room temperature. Claim 17 In claim 16, the first sintering is performed by heating the raw material mixture to a first temperature (T1) and holding it for a first time, then cooling the temperature from T1 to (T1-80)℃ at an average cooling rate of ≤1℃ / min, and satisfying at least one of the following conditions (i) and (ii): (i) if (T1-80)℃ > 800℃, cooling the temperature from (T1-80)℃ to 800℃ at an average cooling rate of ≤1.5℃ / min, then cooling the temperature from (T1-80)℃ to 600℃ at an average cooling rate of ≤2℃ / min, and then cooling naturally to room temperature; (ii) if 600℃ ≤ T1-80℃ ≤ 800℃, cooling the temperature from T1-80℃ to 600℃ at an average cooling rate of ≤2℃ / min, and then cooling naturally to room temperature. Claim 18 In item 15, the above secondary sintered product and the second M 2 A method for manufacturing an anode material, further comprising the step of mixing a source and performing a third sintering on the obtained mixture to obtain a third sintered product. Claim 19 In paragraph 15, the lithium source comprises one of lithium carbonate, lithium hydroxide, anhydrous lithium hydroxide, and lithium oxide; and the M 1 The source is M 1 It comprises at least one of an oxide containing an element, a carbonate, a phosphate, a fluoride, a chloride, a hydroxide, and a silicide; and the first M 2 Source and the 2nd M 2 The sources are each independently M 2 A method for manufacturing an anode material comprising at least one of an oxide containing an element, a carbonate, a phosphate, a fluoride, a chloride, a hydroxide, and a silicide. Claim 20 A method for manufacturing an anode material according to claim 18, wherein the temperature of the second sintering is 400 to 800℃ and the holding time is 4 to 10 hours; the temperature of the third sintering is 300 to 600℃ and the holding time is 4 to 10 hours. Claim 21 A lithium-ion battery comprising a cathode material according to any one of claims 1 to 14. Claim 22 An electrical device comprising a lithium-ion battery according to paragraph 21.
Citation Information
Patent Citations
Method by utilizing X-ray diffraction to measure stress of cubic single-crystal material
CN105136361A
Positive electrode material, preparation method thereof and lithium ion battery
CN118039873A
Lithium ion positive electrode material, lithium ion battery and preparation method
CN118398806A
Cathode materials and their manufacturing methods and applications, lithium-ion battery cathode electrodes and lithium-ion batteries
KR1020230005894A
Cathode material having a multi-cavity structure and a method for manufacturing the same and a lithium ion battery
KR1020230098164A
